Medical students' perceived parental support and its correlation with their motivation to stay in medical school - Peralta, Francesca Karina J.; Viernes, Betsy Joyce E. (College of Home Economics, University of the Philippines Diliman, 2018)
Medical students experience tremendous stress from the demanding nature of studying medicine. With this, the researchers identified medical students current level of motivation and current level of perceived parental support. The relationship of medical students perceived parental support and their motivation to stay in medical school was explored by determining whether the said variables are correlated with each other. The correlation of the two variables were also compared between those whose parents live within and those whose parents live outside Metro Manila. Fifty medical students from medical schools answered an online survey. Data were subjected to quantitative and qualitative analyses, namely, Spearmans Rank-Order Correlation Test and Thematic Analysis. Results showed that the medical students had a moderate level of motivation and a moderate level of perceived parental support. Aside from this, the two variables were found to have a moderate correlation. Lastly, it was discovered that no correlation exists between the two variables for the two groups in the study and this led to a conclusion that geographical distance possibly plays no significant impact in the correlation of the two variables.